(untitled) (ADMPG Journal, 2009)
This study aims at developing a theoretical approach on the effect of different debt-equity ratios on the firm’s market value. It also aims at discussing the relevance of the role of accounting as a source of information about the capital structure and the different costs of capital it includes. Several studies demonstrate that, despite the lack of consensus among theoreticians on the relevance of capital structure in detemining the value of the firm, in practice, the firms tend to manage their sources of financing so that they can get a lower cost of capital, and, consequently, a higher return. The studies also indicate that accounting, by providing relevant information on the capital structure and the costs required from the company by the capital (money) supplier, appears to be important for the decision-making process, allowing a rational decision in order to maximize the value of the firm.